Methodology of training of potential teachers of musical art (on the example of the materials of the virtual tour «Hryhoriy Skovoroda – an artist, philosopher, and educator») - Bezemchuk, L.; Fomin, V. (New Collegium, 2022)
The chosen topic becomes especially relevant in terms of military situation in Ukraine, since some of the sights presented in the photos by the authors in the content of the virtual tour retain their original appearance, which may differ from today. The purpose of the article is to substantiate the practical value of a virtual excursion as an effective methodological aid for teaching the school subjects of the art education during pedagogical practice by potential music teachers in the process of providing distance and mixed forms of education. To select practical material, the authors use bibliographic, historical, systematic, concentric, and problem methods. The content structuring of the virtual excursion dedicated to the figure of H. Skovoroda is an example of a creative project for online work with students online made by the students of the specialty 014 Secondary Education (Musical Art), who will be able to implement it in the professionally oriented disciplines. It includes interesting tasks for high school students’ work upon the compositions of a famous poet, musician, and educator, organized in pair, group and individual forms. The didactic material of the virtual tour was filled based on a systematic analysis of the artist's creative heritage using reproductive and productive methods of high school students’ teaching. The authors took into account the algorithms for developing such a form of work with students as: a plan, choosing places for virtual stops, preparing questions and tasks for discussion and completing them independently or in groups. The online format makes it possible to combine various types of artistic activity of students, helps them find and process the artistic thesaurus faster: where, by whom, under what circumstances was the monument created, whether it was preserved intact, restored, or fully restored; what is the historical and artistic value of the monument. The presentation of the material enables to find answers to the questions raised by the authors during the journey through the virtual steps of the tour, to receive feedback between future teachers and students during the processing of the stops, which become a sort of didactic compass for the analysis of the texts of the musical and poetic heritage of Hryhoriy Skovoroda, the Kharkiv region role in the life and creativity of the world-famous philosopher and educator.